Determinants of Vaccine Hesitancy in Indonesia: A Scoping Review - Hanifah, Nuril; Herdiana, Ike; Ardi, Rahkman (Makara Human Behavior Studies in Asia, 2021)
Complete children immunization coverage in Indonesia declined from 59.2% in 2013 to 57.9% in 2016. Therefore, a study on understanding the vaccination barrier is necessary to improve future coverage. This scoping review aims to identify the determinants of vaccine hesitancy using the model of the World Health Organization-Strategic Advisory Group of Expert (WHO-SAGE) working group and to map them on the basis of region, target population, and vaccine. This research used publications from seven databases (Science Direct, Wiley, Scopus, SAGE, PubMed, Springer, and Taylor & Francis) from 2015 to 2020. A total of 10,212 publications were identified and filtered by employing the PRISMA method, thereby leaving 24 publications that were featured in this review. The majority of these publications is quantitative research conducted in Aceh and Yogyakarta and investigates children complete immunization, with adults and parents being the target population. The vaccine hesitancy determinants that are mentioned the most are social-economy, religion/culture/ gender, the role of health-care professionals, cost, knowledge, and awareness about vaccine, and attitude toward preventive health behavior. However, additional evidence on the influence of contextual-focus factors in various regions in Indonesia is crucial for a further understanding of the antecedent of the relationship between determinant factors and vaccination behavior.